Start-up of horizontal anaerobic reactors with sludge blanket and fixed bed for wastewater treatment from coffee processing by wet method - Oliveira, Roberto A. de [UNESP]; Bruno, Natani M. N. [UNESP] (Associação Brasileira de Engenharia Agrícola (SBEA), 2013)
Foram avaliados os procedimentos de partida de sistema de tratamento com três reatores anaeróbios horizontais (R1, R2 e R3), instalados em série, com volume de 1,2 L cada. O R1 com manta de lodo e o R2 e R3 através de suporte de bambu e fibra de coco, respectivamente. Como afluente,foram sintetizadas águas residuárias do despolpamento mecânico dos frutos do cafeeiro por via úmida, com valor médio de demanda química de oxigênio total (DQOtotal) de 16.003 mg L-1. O tempo de detenção hidráulica (TDH) em cada reator foi de 30 h. As cargas orgânicas volumétricas (COV) no R1 foram de 8,9 a 25,0g DQOtotal (L d)-1. As eficiências de remoção de DQOtotal variaram de 43 a 97% no sistema de tratamento (R1+R2+R3), estabilizando acima de 80% após 30 dias de operação. Os teores médios de metano no biogás foram de 70 a 76%, a produção volumétrica média de 1,7 L CH4 (L reator d)-1 no sistema, e as conversões mais altas, de 0,20 L CH4(g DQOremovida)-1, ocorreram no R1 e R2. Os valores médios de pH nos efluentes foram de 6,8 a 8,3 e de ácidos voláteis totais permaneceram abaixo de 200 mg L-1 no efluente do R3.As concentrações de fenóis totais do afluente variaram de 45 a 278 mg L-1, e a eficiência média de remoção foi de 52%. A partida do sistema de tratamento ocorreu após 30 d, em virtude da inoculação com lodo anaeróbio com microbiota ativa.

In this study it was evaluated the start-up procedures of anaerobic treatment system with three horizontal anaerobic reactors (R1, R2 and R3), installed in series, with volume of 1.2 L each. R1 had sludge blanket, and R2 and R3 had half supporter of bamboo and coconut fiber, respectively. As an affluent, it was synthesized wastewater from mechanical pulping of the coffee fruit by wet method, with a mean value of total chemical oxygen demand (CODtotal) of 16,003 mg L-1. The hydraulic retention time (HRT) in each reactor was 30 h. The volumetric organic loading (VOL) applied in R1 varied from 8.9 to 25.0 g of CODtotal (L d)-1. The mean removal efficiencies of CODtotal varied from 43 to 97% in the treatment system (R1+R2+R3), stabilizing above 80% after 30 days of operation. The mean content of methane in the biogas were of 70 to 76%, the mean volumetric production was 1.7 L CH4 (L reactor d)-1 in the system, and the higher conversions were around at 0.20 L CH4 (g CODremoved)-1 in R1 and R2. The mean values of pH in the effluents ranged from 6.8 to 8.3 and the mean values of total volatile acids remained below 200 mg L-1 in the effluent of R3. The concentrations of total phenols of the affluent ranged from 45 to 278 mg L-1, and the mean removal efficiency was of 52%. The start-up of the anaerobic treatment system occurred after 30 days of operation as a result of inoculation with anaerobic sludge with active microbiota.
Partida de reatores anaeróbios horizontais com manta de lodo e de leito fixo para tratamento de águas residuárias do beneficiamento de frutos do cafeeiro por via úmida
Keywords: carga orgânica volumétrica; bambu; metano; fenóis; reatores em série; volumetric organic loading; bamboo; methane; phenols; reactors in series